Economic Integration and Fiscal Decentralization: Evidence from OECD Countries - Dan Stegarescu (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
Drawing on recent work on the creation and breakup of countries, this paper examines the impact of economic and political integration on the vertical government structure. It argues that by increasing the market size and the benefits from the decentralized provision of public goods, integration might have triggered the recent process of fiscal decentralization in OECD countries. Based on a theoretical framework, the empirical panel analysis relates the degree of public sector decentralization to economic and European integration, controlling for inter-regional heterogeneity, economies of scale, and institutions. The results found mostly support a decentralizing effect of economic and European integration, particularly in the context of preference heterogeneity, whereas participation of sub-national governments in central decision-making is associated with increasing centralization.
Keywords: H77; H72; F15; 330; Fiscal Decentralization; Economic Integration; European Union; ?Sandwich? Hypothesis; Wirtschaftsintegration; Politische Integration; Finanzverfassung; Dezentralisierung; OECD-Staaten